2011
DOI: 10.1371/journal.pone.0017663
|View full text |Cite|
|
Sign up to set email alerts
|

Does Environmental Enrichment Reduce Stress? An Integrated Measure of Corticosterone from Feathers Provides a Novel Perspective

Abstract: Enrichment is widely used as tool for managing fearfulness, undesirable behaviors, and stress in captive animals, and for studying exploration and personality. Inconsistencies in previous studies of physiological and behavioral responses to enrichment led us to hypothesize that enrichment and its removal are stressful environmental changes to which the hormone corticosterone and fearfulness, activity, and exploration behaviors ought to be sensitive. We conducted two experiments with a captive population of wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 71 publications
1
50
0
2
Order By: Relevance
“…By analyzing the plasma-feather relationship on an individual basis, we found that plasma CORT at day 9 correlated positively with whole-feather CORT f . Lattin and colleagues did not detect a relationship between plasma CORT and CORT f from feather sections at any point in their experiment (Lattin et al, 2011); these findings are in contrast to evidence that CORT f from feather sections reflects experimental manipulations occurring during the growth of those sections (Fairhurst et al, 2011). In Lattin and colleagues' study (Lattin et al, 2011), between-group differences in CORT f from sections of feather grown prior to hormone implants may have been influential.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…By analyzing the plasma-feather relationship on an individual basis, we found that plasma CORT at day 9 correlated positively with whole-feather CORT f . Lattin and colleagues did not detect a relationship between plasma CORT and CORT f from feather sections at any point in their experiment (Lattin et al, 2011); these findings are in contrast to evidence that CORT f from feather sections reflects experimental manipulations occurring during the growth of those sections (Fairhurst et al, 2011). In Lattin and colleagues' study (Lattin et al, 2011), between-group differences in CORT f from sections of feather grown prior to hormone implants may have been influential.…”
Section: Discussionmentioning
confidence: 84%
“…Work with birds has shown that feathers contain corticosterone (CORT) (Bortolotti et al, 2008;Koren et al, 2012), the primary avian GC. CORT in feathers (CORT f ) has been correlated with variation in parental provisioning (Fairhurst et al, 2012b), nest box microclimate (Fairhurst et al, 2012a), environmental enrichment (Fairhurst et al, 2011), expression of carotenoid-based signals (Bortolotti et al, 2009b;Mougeot et al, 2010;Kennedy et al, 2013), egg mass (Kouwenberg et al, 2013), stable isotopes of carbon (Fairhurst et al, 2013) and components of fitness (Bortolotti et al, 2008;Koren et al, 2012). This biomarker relates to diverse ecological factors, suggesting that it integrates CORT secretion in general, rather than expresses a response to any specific source of environmental variation.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Environmental enrichment (EE) exposure treatment is widely used for managing fearfulness, abnormal behaviors, and stress in laboratory animals. [14] Exposure to EE was known to enhance spatial memory abilities and synaptic strength in the hippocampus of the brain. [15] EE exposure is known to influence the CNS at the functional, anatomical, and molecular levels, both during the critical period and during adulthood.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…The potential ecological applications of this technique are broad and already the few published studies that employ it address questions ranging from the impact of the pre-breeding body condition on egg production (Kouwenberg et al, 2013) to the effect environmental enrichment has on the physiological state of captive passerines (Fairhurst et al, 2011). There is evidence, however, that during development variations in resource allocation may produce feather CORT results opposite to those expected from plasma CORT studies (Patterson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%